Live births and deaths of neonates born to adolescent mothers: analysis of trends and associations from a population study in a region of a middle-income country - Carina Nunes Vieira e Oliveira; Tulio Konstantyner; Daniela Testoni Costa-Nobre; Ana Sílvia Scavacini Marinonio; Mandira Daripa Kawakami; Rita de Cássia Xavier Balda; Milton Harumi Miyoshi; Adriana Sanudo; Kelsy Catherina Nema Areco; Paulo Bandiera-Paiva; Rosa Maria Vieira de Freitas; Monica La Porte Teixeira; et al. (BMC Pregnancy and Childbirth)
Abstract Background Adolescent pregnancy is associated with adverse outcomes, and although there has been a global decline in the incidence of teenage pregnancies and neonatal deaths, the absolute number remains significant. This study aimed to evaluate temporal trends in live births and neonatal deaths from adolescent mothers, as well as to identify the effect of adolescent pregnancy on neonatal death. Methods This is a population-based study of all live births from mothers residing in Sao Paulo state, Brazil, between 2004 and 2020. The Prais-Winsten model was used to analyze annual trends for live births from adolescent mothers, neonatal mortality rates, and the percentage of neonatal deaths within specific demographic groups. The Kaplan–Meier survival curve evaluated the time to neonatal death. A Poisson regression model was utilized to identify maternal and neonatal characteristics associated with the risk of neonatal death. Results The present study encompassed a total of 9,870,181 live births, with 14.4% occurring to adolescent mothers. There were 75,504 neonatal deaths, with 14,159 (18.8%) of those occurring in the neonates born to adolescent mothers. The annual percentage change in live births to adolescent mothers decreased by -3.03% (95%CI: -4.12% to -1.93%). The neonatal mortality rates showed a declining trend within both adolescent and non-adolescent mothers. Infants born to adolescent mothers had a higher probability of neonatal death and an earlier age of death when compared to non-adolescent mothers’ infants. Poisson multiple regression analysis indicated an elevated risk of neonatal death for seven tested variables (adolescent mothers, inadequate prenatal care, multiple gestation, non-hospital delivery, low birth weight, male sex and congenital anomalies) and a reduction on risk of death for neonates born from cesarean section. Conclusions The study showed a reduction in live births to adolescent mothers and neonatal deaths among adolescent mothers from 2004 to 2020 in the state of Sao Paulo. Was also shown a risk association between been born to adolescent mothers and neonatal death.